2022
DOI: 10.1002/mc.23422
|View full text |Cite
|
Sign up to set email alerts
|

Risk SNP‐mediated LINC01614 upregulation drives head and neck squamous cell carcinoma progression via PI3K/AKT signaling pathway

Abstract: As potential biomarkers and therapeutic targets, long noncoding RNAs (lncRNAs) are involved in the tumorigenesis of various tumors. Genetic variation in long noncoding regions can lead to lncRNA dysfunction and even cancer. Nevertheless, studies on the association between lncRNA‐associated single‐nucleotide polymorphisms (SNPs) and the risk of head and neck squamous cell carcinoma (HNSCC) remain inadequate. Here, we aimed to explore the association between SNPs in LINC01614 and HNSCC risk, and the potential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
3
7
0
Order By: Relevance
“…However, our results show that miR-616 expression attenuates the Furthermore, we observed that expression of miR-616 was reduced in human breast cancers as compared to tumour adjacent normal tissue (Fig 9). In agreement with our results miR-616-3p has been shown to potentiate apoptosis in HUVECs (16), inhibit head and neck squamous cell carcinoma progression (17) and inhibit cell growth and mammosphere formation of breast cancer cells (18,25). Any small RNA having G-rich 6mer seed sequence (nt 2-7 of the guide strand) can reduce viability of cells when associated with RNA-induced silencing complex.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, our results show that miR-616 expression attenuates the Furthermore, we observed that expression of miR-616 was reduced in human breast cancers as compared to tumour adjacent normal tissue (Fig 9). In agreement with our results miR-616-3p has been shown to potentiate apoptosis in HUVECs (16), inhibit head and neck squamous cell carcinoma progression (17) and inhibit cell growth and mammosphere formation of breast cancer cells (18,25). Any small RNA having G-rich 6mer seed sequence (nt 2-7 of the guide strand) can reduce viability of cells when associated with RNA-induced silencing complex.…”
Section: Discussionsupporting
confidence: 92%
“…This cluster maps to a region frequently amplified in Burkitt’s lymphoma, diffuse large B-cell lymphoma, follicular lymphoma and lung cancer (26, 43). The expression of miR-17-92 is reduced in prostate cancer (17) and miR-17-92 expression in intestinal epithelial cells inhibited colon cancer progression by suppressing tumour angiogenesis (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the thermodynamics of RNA-RNA binding plays a crucial role in the interaction of miRNA with target mRNA, it can be expected that sequence variants such as SNP in miRNA binding sites may affect the expression of miRNA targets. There was also evidence that SNPs in miRNA binding sites may be associated with disease, such as SNP identi ed at miRNA binding sites in oncogenes are associated with increased gene expression in papillary thyroid cancer (Hou et al 2022). Due to the mutation of SLC24A5 gene, the golden mutation is accompanied by the decreased pigmentation of the skin melanophore and the retinal epithelium, and the number and density of melanosomes are reduced, resulting in the delay and reduction of melanin deposition (Reis et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the SNP rs11655237 allele G in LINC00673 exon can create a miRNA binding site that increases the function of LINC00667 expression ( Figure 2 e). Furthermore, rs67311347 in RCC [ 109 ], rs12982687 in CRC [ 110 ], and rs16854802 in neck squamous cell carcinoma (HNSCC) [ 111 ] are SNPs in lncRNA sequences that affect target gene expression by binding with miRNA. If a SNP occurs within miRNA, it will consequently affect the binding affinity of the miRNA to target genes.…”
Section: Functional Mechanisms Of Non-coding Region Snpsmentioning
confidence: 99%